1986
DOI: 10.1210/endo-118-4-1353
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Antiserum to Rat Cytochrome P-450 Cholesterol Side Chain Cleavage, and Its Use for Ultrastructural Localization of the Immunoreactive Enzyme by Protein A-Gold Technique*

Abstract: Rabbit antiserum to rat cytochrome P-450 cholesterol side chain cleavage (P-450scc) was produced without a previous biochemical purification of the enzyme. Instead, for immunization we used a single protein band of mol wt 53,000, which was isolated from sodium dodecyl sulfate polyacrylamide gel electrophoresis of rat steroidogenic mitochondrial membranes. The resulting antiserum cross-reacted in a protein-blotting test with affinity purified and biologically active bovine adrenocortical P-450scc enzyme. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(66 citation statements)
references
References 0 publications
4
62
0
Order By: Relevance
“…In all the reactive cell types, immunolabeling was restricted to mitochondria, with gold particles overlying vesicular structures. These results are in agreement with a previous immunoelectron microscopic study indicating that P450 scc immunoactivity was associated with the matrix side of the inner mitochondrial membranes in rat adrenocortical cells as well in granulosa, theca interna and interstitial cells in the ovary (Farkash et al 1986). They are also in agreement with previous subcellular fractionation studies indicating that in rat and bovine adrenal glands P450 scc activity was associated with mitochondrial fractions (Hanukoglu et al 1981, Kramer et al 1984, Cherradi et al 1994.…”
Section: Discussionsupporting
confidence: 92%
“…In all the reactive cell types, immunolabeling was restricted to mitochondria, with gold particles overlying vesicular structures. These results are in agreement with a previous immunoelectron microscopic study indicating that P450 scc immunoactivity was associated with the matrix side of the inner mitochondrial membranes in rat adrenocortical cells as well in granulosa, theca interna and interstitial cells in the ovary (Farkash et al 1986). They are also in agreement with previous subcellular fractionation studies indicating that in rat and bovine adrenal glands P450 scc activity was associated with mitochondrial fractions (Hanukoglu et al 1981, Kramer et al 1984, Cherradi et al 1994.…”
Section: Discussionsupporting
confidence: 92%
“…Higher magnification shows that these mitochondria contain tubulo-vesicular cristae (Fig. 3E), which are typical for cells engaged in active steroidogenesis (Farkash et al, 1986). It indicates that these cells have already acquired steroidogenic potential.…”
Section: Histological Analysis Of the Interrenal Glandmentioning
confidence: 83%
“…Farkash et al (1986) recently demonstrated by ultrastructural immunohistochemistry of P450scc in rat ovary that the transition of lamelliform to tubular mitochondrial cristae was associÂŹ ated with the expression of P-450scc. The prominent immunoreactivity noted in the present study of P-450scc, which is the mitochondrial cytochrome P-450 and is necessary for progesterone synthesis, in luteinized granulosa cells can also reflect increased progesterone production after ovulation.…”
Section: Discussionmentioning
confidence: 98%